Adsorption of Plutonium onto Several Natural Sediments. Issue 2 (February 2022) - Yu, Jing; Zhang, Qingyu
Abstract : Abstract: The adsorption of plutonium (Pu) onto several natural sediments was studied using batch experiments to determine the different factors influencing Pu adsorption. These factors include the possible effect of different methods for adding Pu solution, the initial oxidation state of Pu, the particle size of the sediments, the pH, and the ionic strength of solution. The method used for adding Pu solution greatly influenced the species of Pu in sediment-groundwater systems and the adsorption behavior of Pu onto the sediments. Initial oxidation state of Pu, clay mineral content, particle size of sediment, pH, and ionic strength all appear to impact adsorption. The sediments preferred to adsorb Pu(IV) rather than Pu(V). The adsorption of Pu depended on the particle size and clay mineral content of the sediments; the higher the clay mineral content and the smaller the particle size, the more adsorption for Pu. The insoluble species of Pu formed in sediment-groundwater systems at pH 9.3 resulted in the decrease of adsorption capacity. The adsorption capacity increased with pH increasing at pH < 9. Ion exchange was the dominant mechanism for Pu adsorption onto the sediments at pH < 7.5. It appeared that the ionic strength had a stronger influence on adsorption capacity than pH.